Theoretical Underpinnings of the Political Priorities of Municipal Healthcare Services in Norway<subtitle>How a Rawlsian Heuristic Can Aid Political Decision-Making in Municipal Healthcare Services</subtitle> - Daniel Rød; Vegard Stensen; Martin Sollund Krane (Scandinavian University Press (Universitetsforlaget), 2024)
This paper aims to discuss the current criteria for municipal priorities in municipal healthcare services in Norway in light of major theories from political philosophy on social justice, such as John Rawlsʼs theory of justice and utilitarianism. Our first goal is to show that perspectives from political philosophy could prove useful for increasing our understanding of the current priority-setting criteria in municipal healthcare services. Decision-makers in municipalities often have to exercise discretion in their decisions. We argue that the current criteria of health benefit, resource use and severity can introduce some indeterminacy in certain situations where municipalities have to make priorities. This is important, as municipalities are experiencing an increase in demand coupled with a decrease in capacity due to an ageing population, leading to a stronger need for prioritization between services. Our last goal is to provide a heuristic based on Rawlsʼs Original Position that may help to narrow indeterminacy in choice situations. We have included a case of municipal decision-making that focuses on municipal priority-setting in home care services, including assisted living facilities, nursing homes and preventative measures.